Ego-document «My pages» (1952–1983) by Yanka Bryl in narratological reading - Gubskaya, Olga N. (Journal of the Belarusian State University. Philology, 2021)
The 20th century is characterised by the active development of documentary-fiction (creative non-fiction), factual literature, on the one hand, and research interest in the role of fact in a literary work, on the other. The level of development of literary criticism in the 21st century makes it possible to focus research attention not only on the role of a real fact in a literary work, but, thanks to the discoveries of semiotics and the tools of narratology, on the process actualised by this fact. This refers to the author’s reflection on a certain event, sometimes acting as an impulse for the formation of an expression that is removed from the fact, more voluminous for the fact; an expression that demonstrates both the writer’s worldview and the picture of the culture of a particular epoch as a whole. Such an understanding of the role of a fact in a literary work will allow, firstly, to understand an auto-image, a «self-portrait» of the writer, which sometimes differs from the image recorded by biographers; secondly, it will help to recreate the cultural picture of the world; thirdly, it will allow us to demonstrate the role of documentary and fiction discourses of the ego-document. It is also noted that in Belarusian literature, the concept of ego-document is more capacious (broad) than fact literature, since it not only informs about the presence of factography, but also focuses attention on real writer, on the image of the narrator, and on the image of the author. The opinion is expressed that the ego-document in the Belarusian literature is likely to acquire an independent, separate meaning from the literature of fact. The purpose of the article is to reveal the communicative potential of the ego-text using the techniques of narratology; that is, to analyse a literary work at several textual levels at once: event – narration – discourse, events in the text – historical context, the relationship real author – narrator – reader. The research material is the literary work «Мy pages» (1952–1983) by Yankа Bryl. As a result of the research, the following conclusions are made: there is a fragmentation of the narrative instance in the work: the narrator can act as a chronicler and a witness; the narrative model is created by two types of narrative-diary (autobiographical) and memoir; the work is characterised by a dual chronotope: external, which is characterised by the presence of intentions of the official state discourse – the authoritative word, and internal, outlined by the presence of the author’s word in the work.
Keywords: ego-document; literature of fact; narrative; chronotope; narrator; communicative event